2010
DOI: 10.1038/sc.2010.97
|View full text |Cite
|
Sign up to set email alerts
|

A classification and regression tree to assist clinical decision making in airway management for patients with cervical spinal cord injury

Abstract: Study design: This was a prospective observational study. Objectives: To review airway management of patients with acute cervical spinal cord injury (CSCI) who are admitted to the intensive care unit (ICU) and to develop a classification and regression tree (CART) to direct clinical decision making in airway management. Setting: This study was carried out in Australia. Results: A total of 114 patients were included. Tracheostomy insertion occurred in 68 patients (59.7%). Using CART analysis, it was found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 18 publications
0
29
0
5
Order By: Relevance
“…7,9,22,28 Roth et al 22 found a strong relationship between the FVC and almost all of other pulmonary function tests in patients with acute traumatic SCI. Recently, Berney et al 7 investigated the clinical decision for tracheostomy in patients with CSCI using CART and revealed that the FVC less than 830 mL was the fi rst node in the tree.…”
Section: Discussionmentioning
confidence: 97%
“…7,9,22,28 Roth et al 22 found a strong relationship between the FVC and almost all of other pulmonary function tests in patients with acute traumatic SCI. Recently, Berney et al 7 investigated the clinical decision for tracheostomy in patients with CSCI using CART and revealed that the FVC less than 830 mL was the fi rst node in the tree.…”
Section: Discussionmentioning
confidence: 97%
“…In acute injury, a VC below 10 ml per kilogram of body weight predicts the need for intubation, 22 and the VC influences both the likelihood of tracheostomy and of weaning success. 23 Similarly, in those with chronic SCI, a lower VC is predictive of pulmonary infection 24,25 and mortality risk. 26 Separate analyses found a statistically significant benefit on VC for IMT but not on FVC; however, the mean differences for the two comparisons were within 10 ml.…”
Section: Discussionmentioning
confidence: 99%
“…Another group has shown that the failure rate be lowered by additional assessment of forced vital capacity, the volume of secretion, and pulmonary gas exchange. 9 One or more re-intubations are associated with increased mortality 10,26 and longer ICU and hospital durations. 26 In our study, 78% of all cases were surgically tracheostomized.…”
Section: Discussionmentioning
confidence: 99%
“…Weaning and treatment measures have been shown to influence pulmonary complications. [3][4][5] They include the indication for primary intubation, [6][7][8] attempts at extubation, [8][9][10] tracheostomy, 7,11,12 weaning, and therapeutic measures to combat pulmonary complications.…”
Section: Introductionmentioning
confidence: 99%